2007
DOI: 10.3354/ame047153
|View full text |Cite
|
Sign up to set email alerts
|

Responses of heterotrophic bacteria to solar irradiance in the eastern Pacific Ocean

Abstract: We investigated the effects of sunlight on bacterial 3 H-leucine (Leu) and 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…However, strong light inhibition was also consistently found in the Adriatic (Sommaruga et al 1997) and the areas of upwelling off the Chilean coast (Hernández et al 2006). Both inhibitory and stimulatory effects were reported by Morán et al (2001) and Pakulski et al (2007), who observed interesting differences between substrates, with overall light Leu stimulation but both stimulation and inhibition of TdR incorporation. Aas et al (1996) also noted light TdR inhibition parallel to Leu stimulation in their samples.…”
Section: A Specific Example: the Question Of Light Vs Dark Incubatiomentioning
confidence: 78%
See 3 more Smart Citations
“…However, strong light inhibition was also consistently found in the Adriatic (Sommaruga et al 1997) and the areas of upwelling off the Chilean coast (Hernández et al 2006). Both inhibitory and stimulatory effects were reported by Morán et al (2001) and Pakulski et al (2007), who observed interesting differences between substrates, with overall light Leu stimulation but both stimulation and inhibition of TdR incorporation. Aas et al (1996) also noted light TdR inhibition parallel to Leu stimulation in their samples.…”
Section: A Specific Example: the Question Of Light Vs Dark Incubatiomentioning
confidence: 78%
“…However, incident light, ecosystem trophic status and the composition of bacterial assemblages may help illuminate the elusive question of light vs. dark BP incubations. Thus, higher values of light uptake relative to dark conditions have been found in communities naturally exposed to higher PAR levels along latitudinal (Pakulski et al 2007) or vertical gradients (A. Calvo-Díaz and X. A. G. Morán unpubl.).…”
Section: A Specific Example: the Question Of Light Vs Dark Incubatiomentioning
confidence: 99%
See 2 more Smart Citations
“…This effect varies among environments (Pakulski et al 2007). In some cases, visible light can inhibit leucine incorporation, whereas in other systems, it stimulates incorporation rates.…”
Section: Photoheterotrophic Bacteriamentioning
confidence: 99%